Optimal equity valuation using multiples: The number of comparable firms - Cooper, Ian A.; Lambertides, Neophytos (My University, 2022)
We examine how the accuracy of a multiples-based valuation changes as the number of comparable firms used to estimate the valuation multiple increases. Our research is motivated by a contrast between the approach followed by practitioners, who typically use a small number of closely comparable firms, and the academic literature which often uses all firms in an industry. Using a simple selection rule based on growth rates, we find that using 10 closely comparable firms is as accurate on average as using the entire cross-section of firms in an industry. The loss of accuracy from using five comparable firms rather than 10 firms or the entire industry is not great.
Keywords: Equity valuation; Multiples valuation; Valuation